A test-retest assessment of the effects of mental load on ratings of affect, arousal and perceived exertion during submaximal cycling - Vera, J.; Perales, J. C.; Jiménez, R.; Cárdenas, D. (Journal of Sports Sciences, 2018)
This study aimed to test the effects of mental (i.e. executive) load during a dual physical-mental task on ratings of perceived exertion (RPE), affective valence, and arousal. The protocol included two dual tasks with matched physical demands but different executive demands (2-back and oddball), carried out on different days. The procedure was run twice to assess the sensitivity and stability of RPE, valence and arousal across the two trials. Linear mixed-effects analyses showed less positive valence (-0.44 points on average in a 1-9 scale; Rß2 = 0.074 [CI90%, 0.052-0.098]), and heightened arousal (+0.13 points on average in a 1-9 scale; Rß2 = 0.006 [CI90%, 0.001-0.015]), for the high executive load condition, but showed no effect of mental load on RPE. Separated analyses for the two task trials yielded best-fitting models that were identical across trials for RPE and valence, but not for arousal. Model fitting was improved by assuming a 1-level autoregressive covariance structure for all analyses. In conclusion, executive load during a dual physical-mental task modulates the emotional response to effort, but not RPE. The autoregressive covariance suggests that people tend to anchor estimates on prior ones, which imposes certain limits on scales' usability.